IMPROVING FERTILITY IN POSTPARTUM MARATHWADI ANOESTRUS BUFFALOES USING OVSYNCH AND SEL.ECTSYNCH PROTOCOLS - THORAT, KANCHAN; PATIL, A D; KUMBHAR, U B; GHOKE, S S (The Indian Journal of Animal Reproduction, 2023)
The present experiment was undertaken to study the comparative efficacy of Ovsynch protocol (GnRH +PGF2a +GnRH, Group I) and Selectsynch protocol (GnRH + PGF2" , Group II) for the improvement of fertility inMarathwadi buffaloes. The buffaloes under group I showed induction of oestrus, and conception rate to be 87.50,and 85.71 per cent respectively. The buffaloes under group II responded with induction of oestrus, and conceptionrate by 75.00, and 83.33 per cent respectively. The estrous induction interval and duration of oestrus were foundto be 41 .25 ± 2.26 and 11 .25 ± 0.73 hours in Group I, 29.5 ± 1.65 and 12.25 ± 0.73 in Group II and the duration ofestrous in Group Ill was 10.50 hours.Ovsynch protocol was found to be effective than Selectsynch protocol forimprovement of fertility in post part.um anoestrus Marathwadi buffaloes.
Keywords: Ovsynch; Selectsynch protocol; Fertility improvement; Marathwadi buffalo